Pemanfaatan Rawa Pasang Surut Untuk Tambak Ikan Bandeng - Bayu Aji Girawan; Sugeng Dwi Riyanto; Khoeruddin Wittriansyah Wittriansyah (Politeknik Negeri Cilacap, 2020)
Tritih Lor is a village at Cilacap that consists of swaps that are formed by ocean tides. Our partner as a fish farmer group at Tritih Lor has utilized the swamp for milkfish cultivation to use a traditional system. There are some troubles on their business like the production is too low because they use a traditional system that relies on natural food from a relic carried away by the tides. Another problem that the fish are gone along the tide when the fish pond breaks. To solve that problem, we use a method of repairing the fish pond, install and arrangement of water intake and aeration systems, installation fence around the fish pond, installation of solar panels, pond fertilization, stocking the pond, and harvesting. The result of this activity is an increase in productivity and a decrease in fish mortality. This semi-intensive tidal swamp aquaculture pond can answer the previous problems of traditional cultivation. This activity also can create more technological-based cultivators, make a better income, and increase the usability of the unused land.